Classical Mechanics - Rana, N C; Joag , P S (New Delhi : McGraw Hill, 1991)
The book presents a lucid treatment of classical mechanics with an emphasis on the understanding of the fundamentals. It develops an appreciation of the versatility of practically all the fundamental principles of Physics. The book incorporates the recent developments in classical mechanics over the past four decades, and discusses in detail such topics as constrained systems, Lagrangian and Hamiltonian systems, canonical transformations, Hamilton jacobi theory, small oscillations, rigid body dynamics, central force problems, elasticity and fluid mechanics.
Appendix A1-D 525-589p.; Bibliography 590-593; Index 594-607p.
Keywords: Classical mechanics; Mechanics particle; Physics